Prevalence of sarcopenia and individual- and country-level risk factors in 36 countries: pooled analysis of nationally representative individual data. - Huang, Simu; Lai, Wenyu; Flood, David; Wei, Yuding; Zheng, Yu; Liu, Qitong; Ren, Haoying; Xiong, Suyue; Mansor, Norma; He, Huijing (Age & Ageing, 2026)
Background Sarcopenia is an age-related condition that contributes to disability and healthcare burden worldwide. Yet cross-national evidence on prevalence and multi-level risk factors is limited. Methods We pooled data from 10 nationally representative or population-based ageing studies, including 144 226 adults aged ≥50 years from 36 high- and middle-income countries. Sarcopenia and severe sarcopenia were defined using 2019 revised European Working Group on Sarcopenia in Older People criteria. Prevalence was standardised by age and gender within each country. We examined associations between sarcopenia and individual-level sociodemographic and health characteristics, and country-level socioeconomic indicators. Results Sarcopenia prevalence ranged from 2.1% to 17.4% across 36 countries, with 16 countries above 5.0% and three above 10.0%. Approximately 92.7 million of 1.07 billion adults ≥50 in these countries were projected to have sarcopenia. At the individual-level, higher risk was associated with older age, gender (men), lower education, being unmarried or not partnered, non-full-time employment, lower household wealth, current smoking, non-recent drinking, physical inactivity and ≥2 chronic diseases (e.g. men: RR = 1.47; 95% CI: 1.32, 1.64). At the country-level, higher gross domestic product (GDP) per capita, higher Gender Development Index and lower Labor Force Participation Rate were associated with lower sarcopenia risk (e.g. GDP per capita: RR = 0.42; 95% CI: 0.30, 0.60). Conclusion Sarcopenia varies widely across countries and is more common in middle-income than high-income settings, pointing to a pattern shaped by both personal and contextual conditions. Addressing the emerging burden of sarcopenia will require integrated strategies targeting modifiable risk factors while tackling contextual and structural inequalities.